Rapid erasure of hippocampal memory following inhibition of dentate gyrus granule cells - Madroñal, Noelia; Delgado-García, José M.; Fernández-Guizán, Azahara; Chatterjee, Jayanta; Köhn, Maja; Mattucci, Camilla; Jain, Apar; Tsetsenis, Theodoros; Illarionova, Anna; Grinevich, Valéry; Gross, Cornelius T.; Gruart, Agnès (Nature Communications, 2016)
The hippocampus is critical for the acquisition and retrieval of episodic and contextual memories. Lesions of the dentate gyrus, a principal input of the hippocampus, block memory acquisition, but it remains unclear whether this region also plays a role in memory retrieval. Here we combine cell-type specific neural inhibition with electrophysiological measurements of learning-associated plasticity in behaving mice to demonstrate that dentate gyrus granule cells are not required for memory retrieval, but instead have an unexpected role in memory maintenance. Furthermore, we demonstrate the translational potential of our findings by showing that pharmacological activation of an endogenous inhibitory receptor expressed selectively in dentate gyrus granule cells can induce a rapid loss of hippocampal memory. These findings open a new avenue for the targeted erasure of episodic and contextual memories.